PEMAHAMAN MAHASISWA AGROTEKNOLOGI FAKULTAS PERTANIAN UNIVERSITAS FLORES TENTANG IMPLEMENTASI MERDEKA BELAJAR KAMPUS MERDEKA (MBKM) - Maria Tensiana Tima; Ernesta Leha; Agustinus J.P. Ana Saga (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
Merdeka Belajar Kampus Merdeka (MBKM) is a program that encourages students to master every field of science based on their major so that they are ready to compete internationally. MBKM program is designed to make students obtain the right to study for three semesters in addition to their study program in order to improve their competence, either for their hard or soft skills. The purpose of the study described in this article is to see the Agrotechnology study program students’ understanding and readiness in implementing MBKM. The research method through descriptive qualitative used questionnaires that were filled out by students on the SPADA Dikti link. The results showed that there were 46% of students did not recognize totally about the policy of MBKM and 54% of the students who recognized the policy of MBKM policy, either few, in general, or overall contents of the MBKM policy. Nevertheless, seen from 54% of students who already recognized the policy, 80% of students were ready to contribute to the MBKM activities although there were still 14% who were not ready and 6% of students who were not interested. It proves that Agrotechnology students were ready to take part in MBKM implementation. In addition, it should be conducted socialization completely to make students understand the implementation.